INDONESIAN LANGUAGE AND ARTS - ERNITA DAULAY (UIN Sumatera Utara, 2016)
Indonesia is culturally rich. Indonesian art and culture are intertwined with religion and age-old traditions from the time of early migrants with Western thoughts brought by Portuguese traders and Dutch colonists.The culture of Indonesia has been shaped by long interaction between original indigenous customs and multiple foreign influences.In addition to these basic cultural sensitivities, religion plays a large role in Indonesian life and values. Over eighty-five percent of the people in Indonesia consider themselves Muslims, though their practices differ considerably from Islam as it's practiced in the Middle East. This is because of the rich texture of different religious traditions in the archipelago, from Buddhism and Hinduism to Chinese Confucianism to European Christianity to indigenous animist and ancestor worship practices. For many, the name of Islam is only the sheet that covers the shape of their ancestors' and communities' eclectic spiritual practices. The islands of Indonesia have been major trade hubs for over a thousand years, and each island has its own unique mix of religious traditions and practices depending on who decided to set port there. Therefore, while there are a few religious and spiritual practices that are practiced by a majority of the population, the main rule regarding religion in Indonesia is,